2021
DOI: 10.3390/ani11071897
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Type of Parturition on Colostrum Microbiota Composition and Puppy Survival

Abstract: The objective of our study was to determine whether the type of parturition affects the microbiota of the colostrum and the growth and survival of the puppies. Seventy-nine newborn puppies were divided into three groups regarding the type of parturition: vaginal delivery (VD), elective caesarean section (EL-CS), and emergency caesarean section (EM-CS). After the birth of the puppies, swabs of meconium were collected from the puppies and colostrum was obtained from the dam. Many aerobic and anaerobic bacteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The relationship between colostrum microflora and intestinal microflora of neonates is confirmed by studies in which the composition of meconium collected from neonates was found to be similar to that of colostrum collected from dams [ 61 ]. Adequate microflora composition determines colonization of neonatal intestines, and this directly translates into their chances of survival, adaptation to the ectopic environment, and development of health status [ 60 ].…”
Section: Maternal and Pregnancy-related Factorsmentioning
confidence: 82%
See 4 more Smart Citations
“…The relationship between colostrum microflora and intestinal microflora of neonates is confirmed by studies in which the composition of meconium collected from neonates was found to be similar to that of colostrum collected from dams [ 61 ]. Adequate microflora composition determines colonization of neonatal intestines, and this directly translates into their chances of survival, adaptation to the ectopic environment, and development of health status [ 60 ].…”
Section: Maternal and Pregnancy-related Factorsmentioning
confidence: 82%
“…The colostrum in mammals is the first food of crucial importance for the health of the offspring in the early neonatal period. In canine species, only 5–10% of antibodies can cross the placenta, so newborns are almost completely immune-deficient [ 61 ]. The timing and amount of colostrum intake immediately after birth are important for their survival and future health.…”
Section: Maternal and Pregnancy-related Factorsmentioning
confidence: 99%
See 3 more Smart Citations